THE SMART CITY DASHBOARD : THE OPTIMIZATION OF THE HEALTH SERVICE WITH THE APPLICATION OF THE INFORMATION TECHNOLOGY AT THE COMMUNITY HEALTH CENTER LEVEL - Samsuriah (P3M STMIK Profesional Makassar, 2017)
The research aimed (1) to construct a web-based application which could function as the server; (2) to monitor the development progress of the health services in the Community Health Center. The research used php application with the my sql database with the web display in the form of the health information, particularly in the community health center. The method used was the descriptive method. By conducting the analysis of the basic theories of the smart city, which were modeled and converted into the program language, the application of the smart city dashboard and the optimization of the health service using the application of the information technology at the health center woud be produced. The research result revealed that the output of the point spread of the patients, the data graphic of the patients’ visits showing their ages, the data graphic showing desease groups, and the uploaded patients, including the online maps visualizing the development progress of the services of the health center, which would facilitate the government, patients, and society in general to obtain more detailed information, and hence could make a decision and policy about the services and guaranteed the patients’ comfort in the future.